Development of Socially Responsible Corporate Governance in the Context of Harmonization of Interests of Stakeholders (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article considers objective processes of development of socially responsible corporate governance on the basis of formation of corporate social responsibility of business in Ukraine and substantiates the necessity of forming an organizational-economic mechanism of their management at the level of domestic enterprisestaking into account the coordination of interests of stakeholders.
Keywords: corporate governance, corporate social responsibility, stakeholders